2020
DOI: 10.1021/acsomega.0c01827
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Square RodLike Microtubes Composed of Anatase Nanocuboids with Coexposed {100}, {010}, and {001} Facets for Improved Photocatalytic Performance

Abstract: In this study, hollow square rodlike microtubes composed of anatase nanocuboids with coexposed {100}, {010}, and {001} facets were successfully synthesized via a mild hydrothermal treatment method in the presence of NH4F by using layered H2Ti3O7 ribbons as the precursor. The precursor H2Ti3O7 ribbons were prepared from H+/Na+ ion-exchanged Na2Ti3O7. The suspension solution of protonated H2Ti3O7 ribbons was adjusted to desired pH values (0.5–13.0) prior to hydrothermal treatment. The elongated direction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…26,27 Du et al reported that photocatalytic performance also depends on the exposed facets of TiO 2 . 28,29 The photoactivity of TiO 2 is found to be greatly inuenced by a variety of factors including crystalline phase, specic surface area, crystallinity, photon absorption properties and so on. 1,30 Anatase TiO 2 with higher crystallinity is preferred for photocatalysis, since higher crystallinity would mean fewer defects for the recombination of photogenerated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Du et al reported that photocatalytic performance also depends on the exposed facets of TiO 2 . 28,29 The photoactivity of TiO 2 is found to be greatly inuenced by a variety of factors including crystalline phase, specic surface area, crystallinity, photon absorption properties and so on. 1,30 Anatase TiO 2 with higher crystallinity is preferred for photocatalysis, since higher crystallinity would mean fewer defects for the recombination of photogenerated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…Tetragonal nanorods of anatase crystals consisted of high ratio of lateral (100) facets have been fabricated via immersing alkali titanate nanotubes in basic solution followed with hydrothermal transformation [ 45 ]. In addition, Anatase crystals with elongated truncated tetragonal bipyramids that contains high ratio of (100) facets; enclosed via different types of facets (001), (100) and (101) were fabricated via hydrothermal reaction in aqueous HF solution [ 46 ]. However, still a dilemma to fabricate tetragonal cuboid of anatase crystals enclosed only with (001) and (100) facets.…”
Section: Strategy I: Crystal Facet Engineering Of Tio 2 ...mentioning
confidence: 99%
“…Rounded anatase TiO 2 , rod-like rutile TiO 2 growing along the [001] direction, and plate-like brookite TiO 2 with exposed {111} facets were prepared by hydrothermal treatment of the mixed solution of TiCl 3 and H 2 O 2 with different concentrations under certain pH conditions [21]. Moreover, anatase TiO 2 nanocrystals with exposed {010}, {001}, and {111} facets and rutile TiO 2 nanorods with exposed {110} facets on the lateral surface were also prepared using the layered titanate as the titanium source, which exhibited good photovoltaic performance (5.14%) or superior photocatalytic activity for the degradation of organic rhodamine B (76.0%) and methyl orange (96.5%) molecules [22][23][24].…”
Section: Introductionmentioning
confidence: 99%